2021
DOI: 10.1029/2020jd033187
|View full text |Cite
|
Sign up to set email alerts
|

A Rocket‐Triggered Lightning Flash Containing Negative‐Positive‐Negative Current Polarity Reversal During Its Initial Stage

Abstract: A rocket-triggered lightning flash containing negative-positive-negative current polarity reversal during its initial stage is analyzed using multiple synchronized observation data. The flash was triggered under a thunderstorm transition zone between the convective region and the stratiform region. The upward positive leader branched and developed toward the stratiform region. When the negative initial continuous current was decreasing, a negative stepped leader was transformed from a recoil leader on a preexi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The positive leader propagated northeasterly in the convective line of the thunderstorm, while the negative leader extending the northwest reached the trailing stratiform region, as shown in Figure S12. Similarly, the bipolar rocket-triggered lightning reported by F. Li et al (2021) initiated in the transition zone between convective and stratiform regions, where positive leaders and negative leaders developed horizontally but extended into different directions.…”
Section: Low-frequency Radiation Mapping Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The positive leader propagated northeasterly in the convective line of the thunderstorm, while the negative leader extending the northwest reached the trailing stratiform region, as shown in Figure S12. Similarly, the bipolar rocket-triggered lightning reported by F. Li et al (2021) initiated in the transition zone between convective and stratiform regions, where positive leaders and negative leaders developed horizontally but extended into different directions.…”
Section: Low-frequency Radiation Mapping Resultsmentioning
confidence: 71%
“…The current direction of the leftward leader got reversed after the +RS, as shown in Figures 1g-1i, and such a polarity reversal of an established channel was the core feature of the bipolar lightning. The main concern of researches about bipolar lightning was investigating how such side discharge occurred, where the channel cutoff was often inferred (F. Li et al, 2021;Shi et al, 2018). For bipolar lightning, initial polarity reversal from negative to positive occurs more often (76% or 16/21) than from positive to negative (H. Zhou et al, 2011), which means side discharge in different polarities occurred with asymmetric frequency.…”
Section: Inception Of Side Discharges and Their Universalitymentioning
confidence: 99%
“…Actually, some particular lightning activities, such as the discharge polarity reversals in bipolar CG lightning flashes, are attributed to the recoil leaders. In a bipolar rocket-triggered lightning flash investigated by Li et al (2021), an important factor for the discharge polarity reversal from negative to positive was that the backward portion of the recoil leader developed into a positive charge region, activating a new negative breakdown that spread slowly. In bipolar CG flashes with positive return strokes followed by subsequent negative return strokes, Saba et al (2013) and Tian et al (2016) found that horizontal positive leader channel reactivated in the form of recoil leader and then jointed to the main grounded channel.…”
Section: Discussionmentioning
confidence: 99%
“…It may even play a key role in linking the different charge regions in the cloud (R. J. Jiang et al, 2021) and give rise to the discharge polarity reversal of a few special bipolar cloud-to-ground (CG) lightning flashes (Li et al, 2021;Saba et al, 2013;Tian et al, 2016). Under certain conditions, abundant recoil leaders may occur, forming highly bifurcated lightning tree channels (Warner, 2012;Yuan et al, 2019), and the preconditioning process of the associated routes are sometimes unobvious or undetectable by optical means, indicating a weak or cold nature.…”
mentioning
confidence: 99%
“…VHF interferometry is widely used in lightning research because it gives the dynamic evolution of elevation and azimuth of the lightning radiation source with unique high accuracy in a simple configuration (Hayenga & Warwick, 1981; Shao et al., 1995; Stock et al., 2014; Sun et al., 2014; Ushio et al., 1997). It greatly enriches our knowledge of lightning discharge, such as the fast breakdown of lightning initiation, side discharges along the lightning channel, and lightning‐related high‐energy radiation (Belz et al., 2020; Li et al., 2021; Pu & Cummer, 2019; Rison et al., 2016; Shao et al., 2020; Stock et al., 2017; Tilles et al., 2019; Urbani et al., 2022). One VHF interferometer provides a 2D lightning channel mapping, while two interferometers around 10 km apart can obtain a 3D location (Jensen et al., 2021; Liu et al., 2018; Shao et al., 2023; Sun et al., 2022).…”
Section: Introductionmentioning
confidence: 98%